Implementasi SOAP Web Service Pada Hasil Webcrawling Website SION STIKOM Bali - I Gede Suardika (Sekolah Tinggi Ilmu Komputer YOS SUDARSO Purwokerto, 2017)
SION (http://sion.stikom-bali.ac.id) is a web-based Academic Information System located in Bali STIKOM used by students to get information about the lecture. SION can only be displayed optimally on a desktop computer, laptop, and tablet. SION can not be integrated with other systems in STIKOM Bali which has different infrastructure. In this research, the implementation of SOAP webservice on results webcrawling SION. Data provided by webservice is derived from the crawling on a website SION. Webservice has been successfully implemented on multiple platforms, namely Dot Net Framework, and Web. System testing is done using alpha testing showed that there are no processing errors and functionally release the results as expected. Webservice provides convenience for users in developing client applications. Keywords: Webservice, Webcrawling, SOAP